Tensile deformation and failure of tungsten single crystals. (January 2023) - Butler, Brady; Maynor, Ekaterina; Hurst, M. Taylor; Yadav, Digvijay R.; Xie, Kelvin; Singh, Shri N.; Paramore, James D.
Abstract: The past century has seen extensive research into the deformation behavior of tungsten and tungsten alloys. Research has focused on understanding the flow behavior, work hardening, and mechanisms of brittle fracture to improve the performance of tungsten alloys at low temperatures. While the plastic behavior of tungsten is inherently linked to the mobility of individual dislocations, the collective motion of dislocations has implications for plasticity and the ultimate failure mechanisms observed at low temperatures. This study provides a detailed analysis of deformation mechanisms observed in tungsten single crystals. Microscopy techniques were utilized to explain significant differences in the deformation behavior of tungsten single crystals as a function of orientation. Electron backscatter diffraction was used to study plasticity with orientation imaging techniques. This work reinforces and expands our understanding of the deformation behavior of tungsten by investigating primary causes for failure in single crystals tested along the [001] and [011] tensile axes. Highlights: Tungsten single crystals were tested in tension at room temperature. Fracture and failure behavior of [001] and [011] orientations are discussed. [001] oriented samples experienced diffuse necking, shear banding, and cleavage fracture normal to tensile axis. [011] oriented samples experienced diffuse necking to a "chisel tip". Twinning was not observed.